Unearthing novel fusions as therapeutic targets in solid tumors using targeted RNA sequencing - An, Sungbin; Koh, Hyun Hee; Chang, Eun Sol; Choi, Juyoung; Song, Ji-Young; Lee, Mi-Sook; Choi, Yoon-La (Frontiers in Oncology, 2022)
Detection of oncogenic fusion genes in cancers, particularly in the diagnosis of uncertain tumors, is crucial for determining effective therapeutic strategies. Although novel fusion genes have been discovered through sequencing, verifying their oncogenic potential remain difficult. Therefore, we evaluated the utility of targeted RNA sequencing in 165 tumor samples by identifying known and unknown fusions. Additionally, by applying additional criteria, we discovered eight novel fusion genes that are expected to process oncogenicity. Among the novel fusion genes, RAF1 fusion genes were detected in two cases. PTPRG-RAF1 fusion led to an increase in cell growth; while dabrafenib, a BRAF inhibitor, reduced the growth of cells expressing RAF1. This study demonstrated the utility of RNA panel sequencing as a theragnostic tool and established criteria for identifying oncogenic fusion genes during post-sequencing analysis.